Anthracnose Incidence, Biochemical Changes, Postharvest Quality and Gas Exchange of Chitosan–Coated Papaya - Ali, Asgar (2006)
A study was conducted to investigate the effect of chitosan -1. on growth of Colletotrichum gloeosporioides, the causal organism of anthracnose; 2. mechanisms involved in controlling anthracnose disease; 3. biochemical changes; 4. physico-chemical quality characteristics and extension of storage life; 5. fruit surface study using SEM and 6. gaseous exchange of papaya fruit during storage at 12 + 1°C. Data were analyzed using analysis of variance and differences between treatments mean were determined by LSD. The results revealed that mycelial growth of C. gloeosporioides was reduced significantly (P ≤ 0.05) at all concentrations as compared to the control. The maximum percent inhibition in mycelium growth (100%) was obtained at 2% chitosan. Similarly, conidial germination inhibition was 100% for 2.0% and 80.4% for 1.5% chitosan coating. Microscopic studies revealed that when chitosan solution was brought in direct contact with conidia there were marked deformities accompanied with shrunken conidia cellular damage and finally death of the cells at 1.5 and 2% coatings. Chitosan (1.5%) was found highly effective in reducing of anthracnose disease upto 93.0% during five weeks storage. The reduction was found to be 85.4% during four days of ripening after five weeks of storage. There was no added advantage of 2.0% chitosan on disease reduction during storage. Marked effect on reducing disease demonstrated the fungicidal effect of chitosan. In addition to its direct microbial activity, the study strongly suggested that chitosan induces a series of defense reactions through production of inducible compounds such as phenols, peroxidase, chitinase and β-1, 3-glucanase in papaya fruits with 1.5% chitosan showing greatest activities. 1.5% chitosan coating showed maximum beneficial effect in reducing weight loss, maintaining firmness, delaying changes in peel colour and the slowing changes in soluble solids concentration (SSC) after five weeks of storage. Non-coated and 0.5% coated fruits gave significantly higher SSC compared to fruits coated with higher percentages of chitosan (1, 1.5 and 2%). The titratable acidity declined throughout the storage period with slower rate in coated fruits. Overall sensory assessment of quality after ripening showed fruits were significantly better in quality when coated with 1.5% chitosan which were assigned higher sensory score than 1% chitosan coated fruits. Two percent coated fruits were rated as zero because of their inability to ripen. Scanning Electron Microscopy (SEM) showed that there were no deep cracks on the surface of 1.5% chitosan coated fruits whereas in non-coated fruit cracks were found on the surface after four weeks of storage.